THE DEVELOPMENT BANK OF BRICS - Thiago Ferreira Almeida; Roberto Luiz Silva (BRICS Law Journal, 2018)
This paper takes aim at the international financial system through the lens of the New Development Bank of the BRICS countries with an analysis of the Bank’s impact and relevance vis-à-vis the system. The work compares the traditional characteristics of international development institutions such as the World Bank and financial entities directed by national authorities with international solutions such as the New Development Bank, whose goals are to boost the infrastructure and renewable energy sectors of its five member countries as well as those of other developing countries. The work lays out insightful data on foreign direct investment of BRICS, GDP growth analyses, imports and exports inside and outside the BRICS group for a clearer understanding of the companies and businesses involved in the group. The work highlights an outlook of investment and development engaged in this new form of South-South cooperation which has been created by BRICS.